Kajian Penggunaan Tiga Jenis Stimulan Organik terhadap Produksi Getah Pinus (Pinus merkusii) di BKPH Majenang, KPH Banyumas Barat - Bowo Woesono, Hastanto; Hadi, Didik Surya; Rokayah, Aulia (Jurnal Wana Tropika, 2024)
This research aims to determine the influence of organic stimulants and stimulant concentrations on pine resin production, to obtain alternative stimulants that are safe for the environment and can also increase pine resin production. The research design used a Completely Randomized Design (CRD), with a factorial experiment consisting of two factors, namely the organic stimulant type factor which consisted of 3 levels, namely the stimulant extract of shallots, ginger and galangal and the stimulant concentration, which consisted of 3 levels, namely 100% concentration. , 75% and 50% plus control, so there are 9 treatment combinations. Replication was carried out 6 times so that 54 tree samples were obtained plus 6 control trees, or a total of 60 tree samples. The results of the research showed that the average production of pine resin in the stimulant treatment types of onion, ginger, galangal and control extracts was 76, 28 grams, 76.28 grams, 140.06 grams and 21.23 grams, respectively. The results of the variance analysis show that the type of stimulant shows a very real influence, while the concentration of the organic stimulant shows an insignificant influence. Further test results showed that the organic stimulant galangal extract had a significant difference from the organic stimulants of ginger and shallots, while the organic stimulants of shallots and ginger showed no significant differences. The research results also showed that the sap production of the onion and ginger extract stimulant treatment showed sap production that was not significantly different from the control, however, the galangal extract stimulant treatment showed a significant difference.